2004
DOI: 10.1124/jpet.104.066753
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Characterization of the Novel GABAB Receptor-Positive Modulator GS39783 (N,N′-Dicyclopentyl-2-methylsulfanyl-5-nitro-pyrimidine-4,6-diamine): Anxiolytic-Like Activity without Side Effects Associated with Baclofen or Benzodiazepines

Abstract: The role of GABA B receptors in various behavioral processes has been largely defined using the prototypical GABA B receptor agonist baclofen. However, baclofen induces sedation, hypothermia and muscle relaxation, which may interfere with its use in behavioral paradigms. Although there is much evidence for a role of the inhibitory neurotransmitter GABA in the pathophysiology of anxiety, the role of GABA B receptors in these disorders is largely unclear. We recently identified GS39783 (N,NЈ-dicyclopentyl-2-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
134
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 196 publications
(147 citation statements)
references
References 37 publications
12
134
1
Order By: Relevance
“…53,54 Furthermore, the novel positive GA-BA B R modulator, GS39783, proved to be anxiolytic in, among others, the light-dark box and the elevated plus maze. 55 Our findings agree nicely with these studies, given that the enhanced GABA B R responsiveness of dnActRIB mice was associated with decreased anxiety in the open-field and the lightdark exploration test. Thus it is well conceivable that activin influences anxiety-related behavior also through the modulation of GABA B R-dependent pathways.…”
Section: Discussionsupporting
confidence: 91%
“…53,54 Furthermore, the novel positive GA-BA B R modulator, GS39783, proved to be anxiolytic in, among others, the light-dark box and the elevated plus maze. 55 Our findings agree nicely with these studies, given that the enhanced GABA B R responsiveness of dnActRIB mice was associated with decreased anxiety in the open-field and the lightdark exploration test. Thus it is well conceivable that activin influences anxiety-related behavior also through the modulation of GABA B R-dependent pathways.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, GS-39783 (novel GABA B receptor PAM) was shown to increase in vitro the GABA B receptor agonist affinity and potency, as well as the capacity of GABA to reduce cAMP production (Urwyler et al, 2005). In our hands, this compound exerted the same anxiolyticlike responses on the behavioral level as described elsewhere Cryan et al, 2004;Jacobson and Cryan, 2008). Importantly, we found that a subthreshold dose of GS-39783 (2 mg/kg) was able to counteract to a large extent the anxiogenic effects of CP-55,940 at high dose (Figures 4a-f).…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, GABA B receptorpositive allosteric modulator compounds, such as GS39783 and the more recently synthesized BHF177, are likely to have more subtle effects than GABA B receptor agonists, due to their modulatory, rather than full agonist, properties at the receptors (Guery et al 2007). Accordingly, such compounds do not impair performance in the rotarod test when administered alone (Cryan et al 2004). In a series of recent studies, we demonstrated that several GABA B receptor positive allosteric modulators decreased nicotine selfadministration, decreased break points for nicotine under a progressive ratio schedule of reinforcement and blocked the reward-enhancing effects of nicotine (Paterson et al in press).…”
Section: Neurosubstrates Of Nicotine Reward Dependence and Withdrawalmentioning
confidence: 99%
“…Nonetheless, GABA B receptor agonists have undesirable side effects, including disruption of performance on the rotarod test, a measure of locomotor impairment (Cryan et al 2004), and decreased responding for nondrug rewards, such as food and electrical brain stimulation (Macey et al 2001;Paterson et al 2005a;Slattery et al 2005). Interestingly, GABA B receptorpositive allosteric modulator compounds, such as GS39783 and the more recently synthesized BHF177, are likely to have more subtle effects than GABA B receptor agonists, due to their modulatory, rather than full agonist, properties at the receptors (Guery et al 2007).…”
Section: Neurosubstrates Of Nicotine Reward Dependence and Withdrawalmentioning
confidence: 99%